Odpowiedź :
Cześć!
Rozwiązanie nierówności
[tex](2-x)^2\leq9\\\\2^2-2\cdot2\cdot x+x^2\leq9\\\\x^2-4x+4-9\leq0\\\\x^2-4x-5\leq0\\\\a=1, \ b=-4, \ c=-5\\\\\Delta=b^2-4ac\rightarrow(-4)^2-4\cdot1\cdot(-5)=16+20=36\\\\\sqrt{\Delta}=\sqrt{36}=6\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\rightarrow\frac{-(-4)-6}{2\cdot1}=\frac{4-6}{2}=\frac{-2}{2}=-1\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\rightarrow\frac{-(-4)+6}{2\cdot1}=\frac{4+6}{2}=\frac{10}{2}=5\\\\\huge\boxed{x\in\langle-1;5\rangle}[/tex]
a > 0, ramiona paraboli są skierowane do góry
Odpowiedź:
4-2x<9
-2x<5
2x>-5|/2
x>2½
Szczegółowe wyjaśnienie: